Dampak Penggunaan Gadget Pada Kesehatan Mental Remaja Di SMA Swasta Nur Ihsan Medan - Ekawaty Suryani Mastari; Fitri Aidani Ulfa Hrp; Fahmi Irsan Nasution; Ahmad Yayang Saputra; Jane Alesha (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mental health problems have become an unresolved health problem in the midst of society, both at the global and national levels. Especially during the COVID-19 pandemic, mental health problems will be increasingly difficult to solve. The increasingly worrying condition of people's mental health will affect national productivity. According to WHO, mental health refers to a person's well-being condition, when a person is aware of his or her abilities, is able to manage his or her stress and adapts well, can work productively, and contributes to his environment. Current technological developments also affect mental health, including the use of gadgets. Gadgets make it easy to access information, communicate with others, and do various online activities. However, excessive use of gadgets can have a negative impact on the mental and physical health of users, especially at the age of children and adolescents, The influence of gadgets can result in children being hampered in interacting even in the family environment, easily bored and difficult to concentrate, especially in learning, and interfering with their cognitive development. According to a survey in Indonesia according to Research by Kominfo and the United Nations Children's Fund (2014), the use of social media and digital is an integrated part of the daily life of young people in Indonesia. The study found that 98% of the children and adolescents surveyed knew about the internet and that 79.5% of them were internet users. In addition, there are still few parents who supervise their children when accessing the internet or playing layer media. Prevention and handling of metal health disorders due to the use of gadgets requires the role of various parties, including government policies, parents and families, and the role of the school environment. Socialization in the environment around children, especially schools, is one of the keys.